Políticas de arquivo e gestão de documentos no âmbito da Rede Federal de Educação Profissional, Científica e Tecnológica - Ney Lúcio da Silva (2019)
With Scientific Administration origins, records management is regarded as key to organizations by Archival professionals and scholars for fostering administrative economics, efficiency and efficacy as well as preservation of documents that may have various uses other than the ones that led to their creation. Despite its relevance and urge for implementation, records management is still to be implemented in the long run in a number of organizations. The present study presents and discusses the theoretical and the legal frameworks that guide the theme and may map a context favorable to archive policies and records management, under the light of an institution from the Federal Network of Professional, Scientific and Technological Education, the Federal Center for Technological Education of Minas Gerais. Hence, this research draws relationships between archive public policies, archive institutional policies that is, technical intervention in documents and information. This work is of both exploratory and descriptive nature and encompasses the adoption of case study as a methodological strategy alongside direct observation, documental research, questionnaires, and interviews as data collection procedures. Once the institution is over 100 years, it was aimed at identifying the main initiatives to organize the documents produced/stored in order to clarify its relationship with production, use, assessment criteria and storage of documents over its history. It was worth noting that it is necessary to raise ones awareness of various actors as factors of paramount importance either to archival policy creation in the institutional realm or to records management program implementation.